2019
DOI: 10.3390/ma12162576
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study to Calculate a Structure Conceived by Eugène Viollet-le-Duc in 1850 with Finite Element Analysis

Abstract: This study aims to investigate the application of finite element calculations to mixed structures of complex materials. As an example, we chose a vault designed by Eugène Viollet-le-Duc in 1850, at which time it was not possible to verify the complexities of the different materials working together in a single structure using these calculation methods. To carry out the simulation, the internal qualities of each material and its current equivalent are taken into account. Thus, the composition of each element is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The incorporation of UAV systems in combination with SfM (Structure from Motion) methodologies has generated an immense capacity to study our buildings and historical sites as shown in recent studies [ 12 , 13 , 14 ]. What began as study tools for buildings and archaeological sites [ 15 , 16 ] nowadays has extended to historical urban areas, thanks to the equipment’s improvements (better and lighter cameras and better computers with more computing capacity) and to the powerful SfM process software tools in the field of analysis.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of UAV systems in combination with SfM (Structure from Motion) methodologies has generated an immense capacity to study our buildings and historical sites as shown in recent studies [ 12 , 13 , 14 ]. What began as study tools for buildings and archaeological sites [ 15 , 16 ] nowadays has extended to historical urban areas, thanks to the equipment’s improvements (better and lighter cameras and better computers with more computing capacity) and to the powerful SfM process software tools in the field of analysis.…”
Section: Related Workmentioning
confidence: 99%
“…We can extend the scope of the previous model by adding new layers of information. In this way, as temporal phases, layers of information based (or formed from) on historical documentation can coexist, such as historical photography, historical drawings or even descriptions that help us to model disappeared parts [ 13 , 19 , 20 , 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…Considering the arch as a tri-articulated isostatic structure (Figure 13), we can calculate the support reactions from the three equations of plane statics [39][40][41]. For this purpose, we model uniformly distributed loads in each of the three cases studied, choosing the most unfavourable situation.…”
Section: The Stress Response Of the Structure By A Simplified Modelmentioning
confidence: 99%
“…2020, 10, x FOR PEER REVIEW 4 of 14 understand-know-document, to re-investigate-understand-know-document, and so on as the project was developed). This approach introduced two objectives for the team-first, to define the concept of authenticity so as to apply a consistent methodology [4][5][6][7][8][9], and second, to document the conceptual change that was the confirmation of the first hypothesis in changing the layout of the wall in this section. Hence, the use of photogrammetry, virtual reality, and centimetric data collection resolved both aspects when combined with data output treated with new BIM and HBIM methodologies, which valued what was discovered and updated the obsolete graphics that were in use until now [10][11][12][13][14].…”
Section: Hypotheses and Objectivesmentioning
confidence: 99%